PHYSICO–CHEMICAL PARAMETERS AND BENTHIC MACRO-INVERTEBRATE COMMUNITIES OF CALABAR RIVER, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
A study was conducted to assess the influence of physicochemical parameters on the abundance and distribution of benthic macro–invertebrates in Calabar River (latitude 040 55’ 55” to 050 02’ 50”N; longitude 0080 16’ 35” to 0080 18’ 13.8” E). Five sampling stations labeled stations 1, 2, 3, 4 and 5 respectively, were chosen along the river course. Physicochemical parameters were measured using their respective meters while macro–invertebrates were collected using a Van Veen grab and identified under microscope. Diversity indices; Margaleaf’s (d), Shannon’s (H) and Pielou’s (E) were calculated using their respective formulae. All physico–chemical parameters differed significantly across sampling stations with the exception of temperature and pH. Temperature was lowest (27.520C) at station one and highest (30.300C) at station five while the lowest and the highest average pH were 6.0 at station one, and 6.40 at station three respectively. The lowest DO value (3.10 mg/l) was recorded at station five while stations three and four had the highest value (3.95 mg/l). Lowest and highest BOD were 1.05 mg/l at station one and 2.05 mg/l at station three respectively. TSS was lowest (10.60 mg/l) at station four, and highest (29.05 mg/l) station five while TDS was lowest (19.70 mg/l) in station one and highest (40.80 mg/l) at station five. 5866 macro–invertebrates belonging to different taxa were identified.  Species abundance and diversity indices were generally low, indicating stress in the environment
Keywords: Macro–invertebrates, Physicochemical parameters, Calabar River, Diversity indices, Correlation.